Atual concepção do princípio dispositivo de acordo com os limites objetivos da coisa julgada - Cota Filho, Fernando Rey (2017)
This dissertation aims to investigate deeply the so calles dispositive principle ain order to check if the Brazilian Civil Procedure Code, enacted in 2015, has changed or not (and in which way) the classic definition of the abomementioned principle. In order to do that, it is necessary do establish the premises that will be the object of investigation, starting by the res judicata and its modern concept. Subsequently, the dissertation will then investigate the scope of the civil process, passing through important definition, such as the party request, lide, accion, the congruence principle, and how these institutes have evolved since the enactment od the Brazilian Civil Procedure Code of 1939 until now. All of this in order to seek the possible relevant changes made by the previewsly civil procedures legislations. Then, we will investigate ths objectives limits of res judicata, also from a historical perspective in previews Brazilians procedures code, from 1939, passing by 1973 and then to check how does the current civil procedure code got into this institute. It will also be analysed others institutes that have influence over the abovementioned conception. And then the final chapter will clarify how does the dispositive principle (or even the voluntariness principle) has to be understood by the current civil procedure code. It will be studied if there was any influence from the mentioned institutes on its conception, in order to check if there was any kind of change on its scope and meaning for the CPC/15. The present work seeks to understand what the dispositive principle means, which institutes influence its definition, all that lightened by the objective limits of res judicata as it is on CPC/15